Application of Stem Cells in Stroke: A Multifactorial Approach - Singh, Manisha; Pandey, Pranav K.; Bhasin, Ashu; Padma, M. V.; Mohanty, Sujata (Frontiers in Neuroscience, 2020)
Stroke has a debilitating effect on human body and wrecking effect on the society, with a global incidence of 1 in every 6 people. According to the World Health Organization, 15 million people suffer stroke worldwide each year. Of these, 5 million die and another 5 million are permanently disabled. Motor and cognitive deficits like hemi paresis, paralysis, chronic pain, psychomotor & behavioural symptoms can persist long term and prevent the patient from fully reintegrating into society, therefore remains the costliest healthcare burden. Regenerative medicine using stem cells seems the panacea for sequelae after stroke. Stem Cells based therapy helps in neuro-regeneration and neuro-protection for neurological recovery in patients. However, use of stem cells as a therapy in stroke patients still needs a lot of research at both basic and translational levels. While the mode of action of stem cells in recovering the symptoms is not clear, there are several clinical parameters which need to be addressed before establishing stem cell therapy in stroke, like type of stem cells to be administered, number of stem cells, time of dose, whether dose- busters are required, route of administration, etc. There are upcoming prospects of cell- free therapy also by using exosomes derived from stem cells. There are several ongoing pre- clinical studies aiming to answer these questions. Despite still being in developing stage, stem cell therapy holds great potential in neurological rehabilitation in patients suffering from stroke.